Paroxysmal kinesigenic dyskinesia associated with a novel POLG variant: A case report. Issue 4 (29th January 2021) - Zhou, Yaping; Zhang, Jian; Wang, Xiaoting; Peng, Qian; Shang, Xiuli
Abstract: Introduction: Paroxysmal kinesigenic dyskinesia (PKD) is a rare neurological disease characterized by recurrent dyskinesia or choreoathetosis triggered by sudden movements. Pathogenic variants in PRRT2 are the main cause of PKD. However, only about half of clinically diagnosed PKD patients have PRRT2 mutations, indicating that additional undiscovered causative genes could be implicated. PKD associated with POLG variant has not been reported. Patient concerns: A 14-year-old boy presented with a 2-month history of involuntary dystonic movements triggered by sudden activities. He was conscious during the attacks. Neurological examination, laboratory tests, brain magnetic resonance imaging (MRI), electroencephalogram (EEG) were all normal. Genetic analysis showed a novel variant of POLG (c.440G>T, p.Ser147Ile), which was considered to be a likely pathogenic variant in this case. Diagnoses: The patient was diagnosed with PKD. Interventions: Low dose carbamazepine was used orally for treatment. Outcomes: The patient achieved complete resolution of symptoms without any dyskinesia during the 6-month follow up. Conclusion: Our study identified the novel POLG variant (c.440G>T, p.Ser147Ile) to be a likely pathogenic variant in PKD.